Advanced models for the transfer impedance of metal braids in cable harnesses - Verpoorte, J.; Schippers, H.; Lansink Rotgerink, J.H.G.J. (IEEE, 2018)
Since the development of the model for transfer impedance of metal braids by E.F. Vance, a large number of authors have tried to improve this model in order to make it more accurate and more reliable. The improvements were based on a more accurate physical or electromagnetic description, or on empirical data of a large number of transfer impedance measurements. This paper provides an overview of the specific models for diffusion, hole inductance and braid inductance. In addition to the general overview, a preferred combination of models for the calculation of transfer impedance is presented.